Strengthening Pesantren Through Education Desentralization - Toifur, Toifur (International Conference of Moslem Society, 2018)
Pesantren is acknowledged to have participated in solving the problems of people in various aspects of life, such as education, da'wah, politics, economy, culture, religion, development, and other aspects. The great contribution of pesantren to the people of the nation and state does not then indicate that pesantren is an ideal and criticism-free institution. Many criticisms are addressed to pesantren. This paper is intended to reveal the practice of strengthening pesantren through education decentralization. Strengthening pesantren is aimed at improving the quality and functions of pesantren as one of the important centers of community development as a whole. With its distinct position, pesantren is expected to continually improve its condition and becomes an alternative of people-centered development as well as a value-oriented development center. The era of decentralization of education makes the existence of pesantren an ideal partner for government institutions to jointly improve the quality of existing education as a basis for the implementation of social transformation through the provision of qualified human resources and good moral. The process of social transformation in the current era of autonomy requires regions to be more sensitive to explore local potentials and community needs, so that existing capabilities in society can be optimized. Thus, pesantren should work harder to improve all its shortcomings and add new things to the needs of people of the present time. Therefore, the model of pesantren education based on conventional system today is not enough to assist in the provision of human resources that have integrative competence both in the mastery of religious knowledge, general knowledge, and technological skills.